Pharmacotherapy of Alzheimer’s disease: a thorny road to success - Ibrahim, Nurul Husna; Kumar, Jaya; Mohamed, Wael Mohamed Yousef (Elsevier, 2025)
Neurodegenerative diseases including Alzheimer disease (AD) and Parkinson disease (PD) are characterized by progressive neuronal loss and pathological accumulation of some proteins. Developing new biomarkers for both diseases is highly important for the early diagnosis and possible development of neuroprotective strategies. Currently available treatments for AD only improve the disease symptoms but do not treat the underlying pathophysiological processes. Many drugs targeting the production, aggregation, and clearance of ab plaques failed to give any conclusive clinical outcomes. This mainly stems from the fact that AD is not a disease attributed to a single-gene mutation. Emerging treatments targeting neuroinflammation in AD, such as nonsteroidal antiinflammatory drugs (NSAIDs) and receptor-interacting serine/threonine-protein kinase 1 (RIPK1), restore calcium dyshomeostasis and microglia physiological function in clearing Abeta plaques, respectively, will be deliberately discussed. Other novel pharmacotherapy strategies in treating AD, including disease-modifying agents (DMTs), repurposing of medications used to treat non-AD illnesses, and multitarget-directed ligands (MTDLs) are also reviewed. Furthermore, EBN (Edible Bird Nest) is recently used as complementary medicine in treating AD.